Les restes animaux du sanctuaire gaulois et antique de Mirebeau-sur-Bèze (Côte-d’Or) (fouilles 2001-2007) - Patrice Méniel (Gallia)
48 000 (413 kg) animal bones and teeth are presented. This study provides the main characteristics of animals and bones deposits buried on this complex site between the 2nd century BC and the 3rd century AD. The fauna, dominated by domestic mammals (beef, pork and mutton) shows enough little changes during this long sequence. These animals have been the subject of different types of treatments according to whether they were consumed or not; this results in quite different deposits, with more or less fragmented bones, either isolated or connected. The diversity of these treatments hardly allows us to identify any constants, or establish any analogies with the Gallic sanctuaries we already know.